Increasing Undergraduate Psychology Major's Workforce Readiness Through Courses in Applied Behavior Analysis. (October 2019) - Metzger, Barbara; Gayman, Catherine M.
The American Psychological Association's 2013 guidelines recommend that psychology undergraduate programs make workforce preparation a central feature in undergraduate psychology programs. The addition of courses in applied behavior analysis (ABA) is one method to provide students with the skills and credentials necessary to enter a psychology-related career immediately after graduation. The number of university programs offering coursework in ABA is increasing in tandem with the explosive growth in job opportunities for behavior analysts at both the master's and bachelor's level. We describe Troy University's course sequence in ABA and present some possible challenges for adding coursework in ABA. It is our hope that this article will engender lively intradepartmental discussion about adding courses in ABA to a psychology undergraduate curriculum.